The Crime of Human Trafficking from the Perspective of National and International Law - Daffa Jati Nugroho; Yusuf Saefudin (UM Purwokerto Press, 2023)
Human trafficking is a form of abuse that violates human dignity. Human trafficking in the form of organised crime networks is increasing both domestically and internationally. This organised crime makes it difficult for governments to deal with it and protect its victims. Bloomsbury University refers to human trafficking as